Peranan Kepemimpinan dan Komunikasi untuk Meningkatkan Motivasi Kinerja Anggota Hima Prodi Manajemen UNUSIDA - Nabilla Ayu Az’zahra; Wahyu Eko Pujianto (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze the role of leadership and communication in increasing the performance motivation of student organization members. This research uses a qualitative descriptive method with in-depth interview data collection techniques. The research results show that leadership and communication are two important factors that can increase the performance motivation of student organization members.The head of a student organization has an important role in motivating its members. An effective chairman is able to build trust, reward and provide feedback to his members. Trust can be built through open, honest and transparent communication. Awards can be a form of appreciation for members' hard work and achievements. Positive feedback can increase work motivation by showing members that they are on the right track.Apart from leadership, communication is also an important factor that can increase the performance motivation of student organization members. Effective communication can help leaders to build good relationships with their members, increase work motivation, and achieve organizational goals.